MODEL PEMBELAJARAN PAI DAN BUDI PEKERTI BERBASIS MULTIMEDIA DI MASA PANDEMI COVID-19 (STUDI KASUS DI SMP WAHID HASYIM MALANG) - Muliadi Muliadi; Dzulfikar Rodafi; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The emergence of the covid-19 outbreak impact on several aspects of human life begin from aspect social, economy, religious life and not exception to education which one has been learning process implemented direct face to face with the presence of teacher and students in the class become the learning process implemented in an online way. The event required the Islamic Religious Education teacher at Junior High School Wahid Hasyim Malang plan how the learning model will be used in the online learning process during the covid-19 pandemic. Then by using some research methods, that is observation method, interview method, and documentation method, researcher can collect data from primary data and secondary data. According to the research that has been done, researcher will discuss one of the problem focus which has been formulated, that is how is the model of Islamic Religious Education learning based on multimedia during the covid-19 pandemic at Junor High School Wahid Hasyim Malang. Researcher has acquired some data that the learning model used by Islamic Religious Education teacher at Junior High School Wahid Hasyim Malang, that is use some media (multimedia) have the form of applications, that is WhatsApp, Google form, Classrom, Website and Quizizz.